ANALISIS KINERJA KEUANGAN MENGGUNAKAN ECONOMIC VALUE ADDED, MAKRET VALUE ADDED DAN FINANCIAL VALUE ADDED PADA PERUSAHAAN MAKANAN DAN MINUMAN DI INDEKS KOMPAS100 BEI PERIODE 2018-2020 - Paledung, Marannu; Karamoy, Herman; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2021)
Economic Value Added (EVA), Market Value Added (MVA), and Financial Value Added (FVA) are methods of analyzing financial performance based on value added. The purpose of this study is to analyze the financial performance of food and beverages companies listed in Indeks Kompas100 IDX during 2018-2020. The research method used is qualitative descriptive. The sampling technique used in this study is purposive sampling. A total of six food and beverages companies were used as sample. The result of the study indicates that with the use of EVA method, the companies get negative EVA result (EVA < 0). Only PT Sariguna Primatirta Tbk gets a positive EVA result (EVA > 0) from 2018-2020. Furthermore, with the use of MVA method, all the companies get positive MVA result (MVA >0). With the use of FVA method, all the companies also get positive FVA result (FVA > 0).